Equidade e televisão : o programa Mister Brau, da Rede Globo, e o estímulo à (re)construção do imaginário social do negro no Brasil - Silva, Wagner Machado da (2018)
This study aims to analyze the (in)visibility of black people on television and how this has resulted, over the years, in a devaluation of this ethnic group, contributing to the strengthening of a negative discourse and accentuating inequality in Brazil. Nevertheless, through the insistence and struggle of this subjugated people, a new panorama begins to be perceived in Brazil, where black people’s imagination can be (re)constructed based on TV shows such as Rede Globo’s Mister Brau, and the prominence of black actors provides ownership and empowerment to the population. By analyzing the retrospect of reasons that reified black people and how slavery placed black people in a lower condition, using the methodology of Discursive Textual Analysis, it is possible to understand that black actors Lázaro Ramos and Taís Araújo are managing to gradually deconstruct white hegemony in the media and in the social imaginary and conquer spaces of power, currently being references and a stimulus to the press and society beyond stereotypes. This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) - Finance Code 001.